Fundamental and Technical Analysis of PT Astra International Tbk's Financial Performance for the 2020-2024 Period - Sastiana, Asri; Hanum, Rizki Fadila; Mulyani (PT Katersi Minar Permata, 2025)
The purpose of this study is to evaluate the financial performance of PT Astra International, Tbk in the 2020–2024 period through fundamental and technical analysis approaches. Data sources include annual financial reports and stock price history compiled from the Indonesia Stock Exchange (IDX). Fundamental analysis was conducted using profitability, liquidity, solvency, and activity ratios, while technical analysis was conducted using the moving average (MA) method. The results of the study indicate that PT Astra International Tbk has healthy financial performance and a positive stock price trend, including a 71% increase in EPS, a surge in dividend yield to 12.59% in 2024, and a post-pandemic profit recovery trend. Although stock prices have stagnated since 2022, technical analysis provides positive signals approaching mid-2025. This study provides a comprehensive overview for investors and management in making investment decisions.